Development of a table tennis machine to counter the "chiquita" spin - Ozaki, H.; Tamaki, S.; Ikebukuro, H.; Yamada, K.; Yoshida, K. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
After Beijing Olympics, leading athletes began to use a stroke known as the "Chiquita" spin frequently. Thus, the Japan national table tennis team at the time undertook countermeasures against the Chiquita spin including some plans. However, these did not produce significant results. Therefore, we developed a table tennis training machine for the team in activities supporting the Japan national table tennis team. The machine has 3 rotors to shoot a ball stably. Also, these rotors are twisted to make a "gyro rotation" of the ball. This machine was introduced into the Japan national table tennis team to take measures for London 2012 Olympic.